1989
DOI: 10.1007/bf00718625
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of death in avalanche victims

Abstract: The autopsies of 12 victims from two snow avalanches in North-Norway are reported. Supportive evidence from non-autopsied and surviving victims is included. Consistent autopsy findings were prominent lung oedema, moderate cerebral oedema, extreme contraction of the left ventricle, petechiae in the superior vena cava drainage area, and acute congestion in lungs and kidneys. In four cases in whom no resuscitation was attempted, aortic oxygen pressure was in the range expected in pure asphyxial-type deaths in one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
6

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 5 publications
2
36
0
6
Order By: Relevance
“…Studies of avalanche victims demonstrate a progressive nonlinear reduction in survival as the time of avalanche burial lengthens. 439 -442 The likelihood of survival is minimal when avalanche victims are buried Ͼ35 minutes with an obstructed airway and in cardiac arrest on extrication 440,441,[443][444][445][446][447][448][449] or are buried for any length of time and in cardiac arrest on extrication with an obstructed airway and an initial core temperature of Ͻ32°C. [441][442][443]447,450 It may be difficult to know with any certainty how long an avalanche victim has been buried.…”
Section: Part 1210: Cardiac Arrest In Avalanche Victimsmentioning
confidence: 99%
“…Studies of avalanche victims demonstrate a progressive nonlinear reduction in survival as the time of avalanche burial lengthens. 439 -442 The likelihood of survival is minimal when avalanche victims are buried Ͼ35 minutes with an obstructed airway and in cardiac arrest on extrication 440,441,[443][444][445][446][447][448][449] or are buried for any length of time and in cardiac arrest on extrication with an obstructed airway and an initial core temperature of Ͻ32°C. [441][442][443]447,450 It may be difficult to know with any certainty how long an avalanche victim has been buried.…”
Section: Part 1210: Cardiac Arrest In Avalanche Victimsmentioning
confidence: 99%
“…Based on the low incidence of bradycardia that is resistant to atropine these trials may not be pragmatic or possible. 419,420,[422][423][424][425] ; LOE P4 426,427 ) victims who were buried beyond 35 minutes did not survive if they had an obstructed airway (defined as obstructed by avalanche debris or by other means) on uncovering the head. One study (LOE P5) 428 demonstrated that when breathing in simulated air pockets of different volumes, hypoxia and hypercapnia achieved a steady state after 10 minutes.…”
Section: Knowledge Gapsmentioning
confidence: 99%
“…W literaturze za typową zmianę powszechnie stwierdzaną u ofiar lawin uznaje się obrzęk płuc [14,15]. W przypadkach opisanych w niniejszej pracy -ze względu na zaawansowane zmiany pośmiertne -nie interpretowano obecności płynu w pęcherzykach płuc-nych, ponieważ nie można było określić, czy pojawił się zażyciowo czy w okresie po śmierci, w którym nastąpiły zmiany rozkładowe.…”
Section: Discussionunclassified
“…in victims of avalanches [14,15]. In our case due to the advanced post mortem changes we did not interpret the presence of fluid in the pulmonary alveoli, because it was impossible to determine the time of its appearance (lifetime or the decay-associated period after death).…”
Section: Autorzy Deklarują Brak Konfliktu Interesówmentioning
confidence: 90%